Whole Genome Sequence-Based Identification of Clostridium estertheticum Complex Strains Supports the Need for Taxonomic Reclassification Within the Species Clostridium estertheticum - Wambui, Joseph; Cernela, Nicole; Stevens, Marc J. A.; Stephan, Roger (Frontiers in Microbiology, 2021)
Isolates within the Clostridium estertheticum complex (CEC) have routinely been identified through the 16S rRNA sequence, but the high interspecies sequence similarity reduces the resolution necessary for species level identification and often results in ambiguous taxonomic classification. The current study identified CEC isolates from meat juice (MJS) and bovine fecal samples (BFS) and determined the phylogeny of species within the CEC through whole genome sequence-based analyses. 1,054 MJS were screened for CEC using quantitative real time PCR (qPCR). Strains were isolated from 33 MJS and 34 BFS qPCR-positive samples, respectively. Pan- and core-genome phylogenomics were used to determine the species identity of the isolates. Average nucleotide identity (ANI) and digital DNA-DNA Hybridization (dDDH) were used to validate the species identity. The phylogeny of species within the CEC was determined through a combination of these methods. Twenty-eight clostridia strains were isolated from MJS and BFS samples out of which 13 belonged to CEC. At 95% ANI and 70% dDDH thresholds for speciation, six CEC isolates were identified as genomospecies2 (n = 3), C. tagluense (n = 2) and genomospecies3 (n = 1). Lower thresholds of 94% ANI and 58% dDDH were required for the classification of seven CEC isolates into species C. estertheticum and prevent an overlap between species C. estertheticum and C. frigoriphilum. Combination of the two species and abolishment of current subspecies classification within the species C. estertheticum are proposed. These data demonstrate the suitability of phylogenomics to identify CEC isolates and determine the phylogeny within CEC.